A prenatal case with multiple supernumerary markers identified as derivatives of chromosomes 13, 15, and 20: molecular cytogenetic characterization and review of the literature. (2nd September 2021) - Bertini, Veronica; Giuliani, Cecilia; Ferreri, Maria Immacolata; Orsini, Alessandro; Bonuccelli, Alice; Peroni, Diego; Bonaglia, Clara; Valetto, Angelo
Abstract: Multiple small supernumerary marker chromosomes (sSMCs) are among the rarest cytogenetic abnormalities as they represent roughly 1.4% of cases with sSMCs. We report on a prenatal case presenting de novo multiple sSMCs; these sSMCs were characterized by array CGH and FISH and resulted deriving from three different chromosomes: a der(13), a der(15) and a der(20). The co-presence of der(13), der(20), and der(15) have not been reported yet. The clinical consequences of this marker combination cannot be precisely predicted. However, according to the publicly available databases, the partial trisomies of chromosome 13 and 20 have probably a pathogenic effect. It is worth noting that a cooperative effect, due to interactions among genes harbored on the three derivatives, cannot be excluded, making the genetic counseling challenging.